Podcast
Questions and Answers
Find the difference of the functions f(x) and g(x).
Find the difference of the functions f(x) and g(x).
The difference of the functions f(x) and g(x) is given by $(f-g)(x) = f(x) - g(x) = (3x^2 + 7x) - (2x^2 - x - 1) = x^2 + 8x + 1
Find the sum of the functions f(x) and g(x).
Find the sum of the functions f(x) and g(x).
The sum of the functions f(x) and g(x) is given by $(f+g)(x) = f(x) + g(x) = (3x^2 + 7x) + (2x^2 - x - 1) = 5x^2 + 6x - 1
Find the product of the functions f(x) and g(x).
Find the product of the functions f(x) and g(x).
The product of the functions f(x) and g(x) is given by $(f \cdot g)(x) = f(x) \cdot g(x) = (3x^2 - 2x + 1)(x - 4) = 3x^3 - 14x^2 + 9x - 4
Find the quotient of the functions f(x) and g(x).
Find the quotient of the functions f(x) and g(x).
Calculate the value of f(2) + g(2).
Calculate the value of f(2) + g(2).